REVIEW OF INTERMODAL INTEGRATION FACILITIES AT TELUK BUNGUS FERRY PORT WEST SUMATRA PROVINCE - Khairani, Muhammad; Agustini, Elfita; Diani, Oktrianti; Hanaya, Khansa Putri (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2025)
Teluk Bungus Ferry Port is a port located in Padang City, serving four ferry routes, namely Padang–Tua Pejat, Padang–Sikakap, Padang–Sikabaluan, and Padang–Siberut with two ships. Based on the results of a four-month survey, it shows the lack of intermodal integration facilities such as bus stops, sidewalks, information boards, and signs in public stopping areas. This study aims to design a concept for connecting infrastructure between ships and other modes of transportation through observation methods of facility conditions and vehicle and passenger flow patterns at the port. Based on the analysis, the construction of intermodal integration facilities is needed, including bus stops within the port, pedestrian facilities, information boards, and bus stop signs. The resulting design includes a bus stop measuring 5.7 meters x 2 meters, a 1.85-meter-wide sidewalk equipped with guiding blocks. The information boards are designed to display schedules, routes, transportation fares, and bus stop signs. These facilities are planned to improve the comfort and safety of service users continuing their journeys using public transportation.